Discovery of new cyanopyridine/chalcone hybrids as dual inhibitors of EGFR/BRAFV600E with promising antiproliferative properties. Issue 4 (16th December 2022) - Abou‐Zied, Hesham A.; Beshr, Eman A. M.; Gomaa, Hesham A. M.; Mostafa, Yaser A.; Youssif, Bahaa G. M.; Hayallah, Alaa M.; Abdel‐Aziz, Mohamed
Abstract: As dual EGFR and BRAF V600E inhibitors, 2‐(3‐cyano‐4, 6‐bis(aryl)‐2‐oxo‐1, 2‐dihydropyridine‐1‐yl)‐ N ‐(4‐cinnamoylphenyl) acetamide derivatives 8–20 were developed. Compounds 8, 12, and 13 showed strong antiproliferative activity when the target compounds were synthesized and tested in vitro against four cancer cell lines. These hybrids have a dual inhibition activity on EGFR and BRAF V600E, according to in vitro studies. The EGFR was inhibited by compounds 8, 12, and 13 with IC50 values between 89 and 110 nM, which were equivalent to those of erlotinib (IC50  = 80 nm). Compound 13 was found to be an effective inhibitor of the proliferation of cancer cells (GI50  = 0.72 µM) and demonstrated hopeful inhibitory activity of BRAF V600E (IC50  = 58 nm), which is superior to erlotinib (IC50  = 65 nm). Compound 13 caused apoptosis and showed cell cycle arrest in the G0/G1phase in a study on the MCF‐7 cell line. The new compounds can fit tightly into the active sites of EGFR and BRAF V600E kinases, according to molecular docking analyses. Abstract : 2‐(3‐Cyano‐4, 6‐bis(aryl)‐2‐oxo‐1, 2‐dihydropyridine‐1‐yl)‐ N ‐(4‐cinnamoylphenyl)acetamide derivatives 8–20 were designed and tested as dual EGFR and BRAF V600E inhibitors. Compounds 8, 12, and 13 with dual inhibition activity showed strong antiproliferative potential on four cancer cell lines. The new compounds can fit tightly into the active sites of the EGFR and BRAF V600E kinases.